Pengaruh Sarana & Prasarana Mata Pelajaran Pendidikan Jasmani Terhadap Minat Belajar Siswa Kelas X SMK NEGERI 2 LUWU UTARA - Samsuri, Fhadil Hidayat; Hidayat, Rachmat; Saman, Saman; Riswanto, Andi Heri; Jalil, Rasyidah (Universitas Hamzanwadi, 2025)
This study aims to measure the extent to which physical education facilities and infrastructure affect class X students' interest in learning at SMKN 2 North Luwu. Using a quantitative descriptive method with a correlational approach, this study involved 226 students as a population and 33 students as a sample, selected through purposive random sampling technique. Data were collected through observation, questionnaire, and documentation. The results of the analysis show that 36% of facilities and infrastructure are in the medium category, while 43% of interest in learning is in the low category. The regression test resulted in an F value of 23.418 and a significance value of 0.000, indicating a significant influence between facilities and infrastructure and interest in learning. The R value of 0.612 indicates that facilities and infrastructure have a strong relationship in influencing interest in learning.